Exportação de gado vivo por vias marítimas no Brasil: uma análise histórica, econômica e jurídica - (:unkn) unknown (Universidade Federal do Pampa, 2025)
This article addresses the historical, economic, and legal aspects of the export of live cattle by sea in Brazil, a practice that influences Brazilian foreign trade but is surrounded by controversies and allegations of poor transport conditions, considered by its critics as violations of animal rights. The research employs the deductive method through a qualitative approach, analyzing the content of judicial decisions within a single legal case. It is carried out through bibliographic review and documentary analysis of rulgments, as well as the reading of books, academic journals, and news reports. The objective of this article is to present and analyze the arguments for and against the practice of exporting live cattle from Brazil, as expressed in two judicial decisions. The first is a preliminary injunction resulting from Public Civil Action No. 5000325-94.2017.403.6135, filed by the National Forum for the Protection and Defense of Animals against the Federal Government, aiming to prohibit the export of live animals by ship departing from Brazilian ports. This ruling granted the plaintiff's request and prevented the departure of the ship NADA from the port of Santos, which was carrying 20,000 head of cattle destined for Turkey. The second decision, rendered in the appeals phase by the Federal Regional Court of the 3rd Region (TRF-3), suspended the preliminary injunction and allowed the export to proceed. The controversy surrounding the export of live cattle in Brazil reflects a broader context involving economic, cultural, moral, and legal issues. Supporters of this practice argue that it generates employment and income, boosts the economy, and strengthens international trade with importing countries. Moreover, it is emphasized that this activity is regulated by the Brazilian government, which establishes protocols related to animal health and welfare. Opponents, however, argue that the practice violates constitutional laws that prohibit cruelty against animals, as the animals are often transported in conditions that contravene legal norms—without food and water, under thermal stress, with many being injured or dying during the journey, in addition to the poor hygienic and sanitary conditions.
Live cattle export by sea in Brazil: a historical, economic and legal analysis
Keywords: Exportação de gado vivo; Direito animal; Ação civil pública; Live cattle exports; Animal law; Public civil action; CIENCIAS SOCIAIS APLICADAS